Development of health behaviour questionnaire for breast cancer women in Mainland China - Hui Xu; Guichun Jiang; Xiujie Zhang; Daqiu Wang; Lei Xu; Aiping Wang (Wiley, 2021)
Abstract Aim To develop a questionnaire on the health behaviour of breast cancer women with adjuvant endocrine therapy and to test its reliability and validity. Design An instrument‐development study was applied that comprised three steps: conceptualization, item generation, content validity and field testing of the health behavior properties. Methods On the basis of literature review, the conceptual framework and initial items of each dimension of were designed. The questionnaire investigation was divided into two steps: pre‐experiment (group 1) and psychometrics evaluation (group 2). Correlation procedure and factor analysis were employed to rescreen the items. Reliability testing and validity testing were conducted to analyse the psychometric properties of questionnaire. Results Exploratory and confirmatory factor analyses yielded a five‐factor solution. Cronbach's α was 0.93, the sub‐semi‐reliability of the questionnaire was 0.79 and internal consistency coefficients was 0.70.